To solve the system by substitution, we will solve one of the equations for one variable and substitute it into the other equation.
Let's solve the second equation for y:
3.25x - y = -0.75
Add y to both sides of the equation:
3.25x = y - 0.75
Now, let's substitute this expression for y in the first equation:
-4.5x - 2(y - 0.75) = -12.5
Distribute the -2 to both terms inside the parentheses:
-4.5x - 2y + 1.5 = -12.5
Combine like terms:
-4.5x - 2y = -14
Now we have a new equation:
-4.5x - 2y = -14
Let's solve this equation for x:
-4.5x = -2y - 14
Divide both sides of the equation by -4.5:
x = (-2y - 14) / -4.5
Now we can substitute this expression for x in the equation -4.5x - 2y = -14:
-4.5((-2y - 14) / -4.5) - 2y = -14
Simplify:
2y + 14 - 2y = -14
The y terms cancel out:
14 = -14
This equation is not true, which means there is no solution to the system of equations by substitution.
3 of 33 of 3 Items
Question
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided.
Solve the system by substitution.
{−4.5x−2y=−12.53.25x−y=−0.75
(3 points)
1 answer